2022
DOI: 10.3390/cancers14122994
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Therapy for Acute Myeloid Leukemia: Where Do We Stand?

Abstract: Immunotherapy is changing the therapeutic landscape of many hematologic diseases, with immune checkpoint inhibitors, bispecific antibodies, and CAR-T therapies being its greatest expression. Unfortunately, immunotherapy in acute myeloid leukemia (AML) has given less brilliant results up to now, and the only approved drug is the antiCD33 antibody-drug conjugate gemtuzumab ozogamicin. A promising field of research in AML therapy relies on anti-leukemic vaccination to induce remission or prevent disease relapse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The blockade of the PD-1-PD-L1 interaction significantly enhanced AMG330-induced leukemia cell lysis, T-cell proliferation, and IFNγ secretion [86]. Another emerging immunotherapeutic strategy against AML is represented by cancer vaccination, which can be mainly categorized into peptide vaccines and dendritic cell (DC)-based vaccines [87]. The main goal of AML vaccines is to elicit an effective cellular and/or humoral immune response.…”
Section: Immunotherapy In Aml With Adverse Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blockade of the PD-1-PD-L1 interaction significantly enhanced AMG330-induced leukemia cell lysis, T-cell proliferation, and IFNγ secretion [86]. Another emerging immunotherapeutic strategy against AML is represented by cancer vaccination, which can be mainly categorized into peptide vaccines and dendritic cell (DC)-based vaccines [87]. The main goal of AML vaccines is to elicit an effective cellular and/or humoral immune response.…”
Section: Immunotherapy In Aml With Adverse Geneticsmentioning
confidence: 99%
“…The main goal of AML vaccines is to elicit an effective cellular and/or humoral immune response. To this end, leukemia-associated antigens (LAAs) should be highly expressed, immunogenic, and (mainly) restricted to leukemic cells [87]. LAAs more extensively investigated in phase I or II trials are Wilms tumor (WT1), mucin 1 protein (MUC1), proteinase 3 (PR3), and the receptor for hyaluronic acid-mediated motility (RHAMM), which is found overexpressed in >80% of AML patients [88]; based on the results from early trials, the setting that more likely could benefit more from interventions with peptide vaccines is represented by patients in CR or with minimal residual disease.…”
Section: Immunotherapy In Aml With Adverse Geneticsmentioning
confidence: 99%
“…Currently, there are several types of cancer vaccines explored in clinical trials, including DNA, peptides, dendritic cells (DCs) and RNA [ 10 ]. But for AML, only peptide and DC-based vaccines had been investigated to enhance leukemia-specific immune responses [ 11 ]. A phase II trial of WT1 (Wilms’ Tumor 1) peptide vaccination administered to 22 AML patients with a median age of 64 years after complete remission (CR1) showed that WT1 vaccinations in AML patients were safe and well tolerated, the median disease-free survival (DFS) from CR1 was 16.9 months, while the overall survival (OS) from diagnosis had not yet been reached but is poised to be ≥ 67.6 months [ 12 ], which were superior to published data for similar patients treated with conventional postremission therapies or HSCT [ 13 ], [ 14 ], [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The WT1 gene is highly expressed in hematopoietic and various solid tumors, and cancer immunotherapies targeting WT1 protein have been developed [ 6 8 ]. Regarding WT1 peptide vaccines, however, there are few reports of studies that have verified its clinical usefulness based on randomized trials.…”
Section: Introductionmentioning
confidence: 99%